Alternative energy sources for agricultural production and processing in Nigeria - Onyema, Mac-Anthony Chukwuka (International Food Policy Research Institute, 2010)
Around the world, it is recognized in agricultural production and processing that energy (farm power) is perhaps the second most important input besides land). Yet the agricultural sector in Nigeria has access to less than one percent of the total conventional energy supply in the country (EarthTrends 2003). This brief explores solutions to the rural area energy gap by reviewing the potential for conventional and alternative sources of energy for agricultural production and processing.